Implementing a Kidney Screening Process for Diabetic Patients in a Primary Care Office - Baumgartner, Elizabeth (My University, 2021)
Diabetes is the leading cause of kidney disease worldwide. Screening diabetic patients with microalbuminuria is an easy and inexpensive way to detect kidney disease in the early stages. A quality improvement project was designed to assist a primary care office in developing a standardized process and revising a protocol to increase diabetic kidney screening. The project's goal was to align with the Medicare and Medicaid 2019 benchmark of 95% in screening individuals with diabetes for chronic kidney disease. The project included revising a screening protocol, staff education followed by a questionnaire, and distributing visual kidney screening posters. The plan-do-study-act (PDSA) model guided project implementation. Diabetic kidney screening was tracked over a 12-week period. Out of 399 eligible patients due for a diabetic chronic kidney disease screening, 377 were screened (96%). This project addressed objectives related to Healthy People 2020 by increasing diabetic kidney screening, increasing the number of individuals aware of having kidney disease, and decreasing the overall burden of kidney disease. This project aligns with Triple Aim Initiatives to reduce cost, improve quality of health care and health in the diabetic population.
Keywords: Diabetic kidney disease, micro-albuminuria screening, primary care, screening diabetics for kidney disease